Synthesis and characterization of S,N-heterotetracenes - Vogt, Astrid; Henne, Florian; Wetzel, Christoph; Mena-Osteritz, Elena; Bäuerle, Peter (Beilstein Journal of Organic Chemistry, 2020)
The synthesis and optoelectronic properties of novel S,N-heterotetracenes consisting of fused heterocyclic thiophene and pyrrole rings are presented. Tetracyclic and benzannulated derivatives with a varying number and sequence of sulfur and nitrogen heteroatoms were synthesized in multistep synthetic routes. A Buchwald–Hartwig amination of brominated precursors, thermolysis of azide precursors, and a Cadogan reaction of nitro-substituted precursors were successfully applied to eventually build-up pyrrole rings to stable and soluble fused systems. The various obtained heteroatom sequences ‘SSNS’ (SN4), ‘SNNS’ (SN4’’), and ‘NSSN’ (SN4’) allowed for evaluation of structure–property relationships relative to the sulfur analogue tetrathienoacene (‘SSSS’). In line with the results for the whole series of S,N-heteroacenes, we find that replacement of sulfur by nitrogen atoms in the tetra- and hexacyclic systems leads to a red-shift in absorption, a decrease in oxidation potential and energy gap. On the other hand, the replacement of a thiophene ring by benzene leads to the opposite effects.
Keywords: Buchwald–Hartwig amination; Cadogan reaction; optoelectronic properties; S,N-heteroacene; structure–property relationship

(untitled) - Wang, C.; Dong, H.; Hu, W.; Liu, Y.; Zhu, D. (Chem. Rev., 2012)

(untitled) - Wu, W.; Liu, Y.; Zhu, D. (Chem. Soc. Rev., 2010)

(untitled) - Mori, T.; Nishimura, T.; Yamamoto, T.; Doi, I.; Miyazaki, E.; Osaka, I.; Takimiya, K. (J. Am. Chem. Soc., 2013)

(untitled) - Aragó, J.; Viruela, P. M.; Ortí, E.; Malavé Osuna, R.; Vercelli, B.; Zotti, G.; Hernández, V.; López Navarrete, J. T.; Henssler, J. T.; Matzger, A. J.; Suzuki, Y.; Yamaguchi, S. (Chem. – Eur. J., 2010)

(untitled) - Okamoto, T.; Kudoh, K.; Wakamiya, A.; Yamaguchi, S. (Chem. – Eur. J., 2007)

(untitled) - Zhang, X.; Côté, A. P.; Matzger, A. J. (J. Am. Chem. Soc., 2005)

(untitled) - Wetzel, C.; Brier, E.; Vogt, A.; Mishra, A.; Mena-Osteritz, E.; Bäuerle, P. (Angew. Chem., Int. Ed., 2015)

(untitled) - Snyder, H. R.; Carpino, L. A.; Zack, J. F., Jr; Mills, J. F. (J. Am. Chem. Soc., 1957)

(untitled) - Zanirato, P.; Spagnolo, P.; Zanardi, G. (J. Chem. Soc., Perkin Trans. 1, 1983)

(untitled) - Bulumulla, C.; Gunawardhana, R.; Gamage, P. L.; Miller, J. T.; Kularatne, R. N.; Biewer, M. C.; Stefan, M. C. (ACS Appl. Mater. Interfaces, 2020)

(untitled) - Ogawa, K.; Rasmussen, S. C. (J. Org. Chem., 2003)

(untitled) - Nozaki, K.; Takahashi, K.; Nakano, K.; Hiyama, T.; Tang, H.-Z.; Fujiki, M.; Yamaguchi, S.; Tamao, K. (Angew. Chem., Int. Ed., 2003)

(untitled) - Mitsudo, K.; Shimohara, S.; Mizoguchi, J.; Mandai, H.; Suga, S. (Org. Lett., 2012)

(untitled) - Wetzel, C.; Vogt, A.; Rudnick, A.; Mena-Osteritz, E.; Köhler, A.; Bäuerle, P. (Org. Chem. Front., 2017)

(untitled) - Rudnick, A.; Wetzel, C.; Tscheuschner, S.; Schmalz, H.; Vogt, A.; Greiner, A.; Bässler, H.; Mena-Osteritz, E.; Bäuerle, P.; Köhler, A. (J. Phys. Chem. B, 2017)

(untitled) - Brier, E.; Wetzel, C.; Bauer, M.; Mena-Osteritz, E.; Wunderlin, M.; Bäuerle, P. (Chem. Mater., 2019)

(untitled) - Ata, I.; Dkhil, S. B.; Pfannmöller, M.; Bals, S.; Duché, D.; Simon, J.-J.; Koganezawa, T.; Yoshimoto, N.; Videlot-Ackermann, C.; Margeat, O.; Ackermann, J.; Bäuerle, P. (Org. Chem. Front., 2017)

(untitled) - Mishra, A.; Popovic, D.; Vogt, A.; Kast, H.; Leitner, T.; Walzer, K.; Pfeiffer, M.; Mena-Osteritz, E.; Bäuerle, P. (Adv. Mater. (Weinheim, Ger.), 2014)

(untitled) - Leitner, T. D.; Vogt, A.; Popović, D.; Mena-Osteritz, E.; Walzer, K.; Pfeiffer, M.; Bäuerle, P. (Mater. Chem. Front., 2018)

(untitled) - Chen, X.; Liu, H.; Xia, L.; Hayat, T.; Alsaedi, A.; Tan, Z. (Chem. Commun., 2019)

(untitled) - Steck, C.; Franckevičius, M.; Zakeeruddin, S. M.; Mishra, A.; Bäuerle, P.; Grätzel, M. (J. Mater. Chem. A, 2015)

(untitled) - Meng, L.; Xia, D.; Liu, S.; Yi, X.; Ding, F.; Fan, R.; Yang, Y. (Chem. Lett., 2020)

(untitled) - Wetzel, C.; Mishra, A.; Mena-Osteritz, E.; Walzer, K.; Pfeiffer, M.; Bäuerle, P. (J. Mater. Chem. C, 2016)

(untitled) - Wang, C.-K.; Jiang, B.-H.; Lu, J.-H.; Cheng, M.-T.; Jeng, R.-J.; Lu, Y.-W.; Chen, C.-P.; Wong, K.-T. (ChemSusChem, 2020)

(untitled) - Huang, C.; Liao, X.; Gao, K.; Zuo, L.; Lin, F.; Shi, X.; Li, C.-Z.; Liu, H.; Li, X.; Liu, F.; Chen, Y.; Chen, H.; et al. (Chem. Mater., 2018)

(untitled) - Arora, N.; Wetzel, C.; Dar, M. I.; Mishra, A.; Yadav, P.; Steck, C.; Zakeeruddin, S. M.; Bäuerle, P.; Grätzel, M. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Huang, Y.-F.; Wang, C.-K.; Lai, B.-H.; Chung, C.-L.; Chen, C.-Y.; Ciou, G.-T.; Wong, K.-T.; Wang, C.-L. (ACS Appl. Mater. Interfaces, 2019)

(untitled) - De Simone, B. C.; Marino, T.; Prejanò, M.; Russo, N. (Theor. Chem. Acc., 2016)

(untitled) - Biswas, S.; Pramanik, A.; Pal, S.; Sarkar, P. (J. Phys. Chem. C, 2017)

(untitled) - Roy, P.; Biswas, S.; Pramanik, A.; Sarkar, P. (Chem. Phys. Lett., 2018)

(untitled) - Mazaki, Y.; Kobayashi, K. (Tetrahedron Lett., 1989)

(untitled) - Youn, J.; Huang, P.-Y.; Huang, Y.-W.; Chen, M.-C.; Lin, Y.-J.; Huang, H.; Ortiz, R. P.; Stern, C.; Chung, M.-C.; Feng, C.-Y.; Chen, L.-H.; Facchetti, A.; et al. (Adv. Funct. Mater., 2012)

(untitled) - Wang, Z.; Liang, M.; Dong, H.; Gao, P.; Su, Y.; Cai, P.; Ding, S.; Chen, J.; Xue, S. (Org. Lett., 2017)

(untitled) - Tasior, M.; Czichy, M.; Łapkowski, M.; Gryko, D. T. (Chem. – Asian J., 2018)

(untitled) - Janiga, A.; Krzeszewski, M.; Gryko, D. T. (Chem. – Asian J., 2015)

Novel Thiophene-Pyrrole-Containing S,N-Heteroacenes: Synthesis, Characterization, and Application in Organic Solar Cells - Wetzel, C. (University of Ulm, 2016)

(untitled) - Fuller, L. S.; Iddon, B.; Smith, K. A. (J. Chem. Soc., Perkin Trans. 1, 1997)

(untitled) - Dogru, M.; Handloser, M.; Auras, F.; Kunz, T.; Medina, D.; Hartschuh, A.; Knochel, P.; Bein, T. (Angew. Chem., Int. Ed., 2013)

(untitled) - Kaur, M.; Kumar, R. (ChemistrySelect, 2018)

(untitled) - Freeman, A. W.; Urvoy, M.; Criswell, M. E. (J. Org. Chem., 2005)

(untitled) - Balaji, G.; Phua, D. I.; Shim, W. L.; Valiyaveettil, S. (Org. Lett., 2010)

(untitled) - Qi, T.; Guo, Y.; Liu, Y.; Xi, H.; Zhang, H.; Gao, X.; Liu, Y.; Lu, K.; Du, C.; Yu, G.; Zhu, D. (Chem. Commun., 2008)

(untitled) - Balaji, G.; Della Pelle, A. M.; Popere, B. C.; Chandrasekaran, A.; Thayumanavan, S. (Org. Biomol. Chem., 2012)

(untitled) - Förtsch, S.; Vogt, A.; Bäuerle, P. (J. Phys. Org. Chem., 2017)

(untitled) - O'Brien, A. G.; Lévesque, F.; Seeberger, P. H. (Chem. Commun., 2011)

(untitled) - Srinivasan, S.; Schuster, G. B. (Org. Lett., 2008)

(untitled) - Zhou, J.; Tang, R.; Wang, X.; Zhang, W.; Zhuang, X.; Zhang, F. (J. Mater. Chem. C, 2016)